Work Life Balance and Burnout on Temporary Employees Performance - Elida Gultom; Jeli Nata Liyas (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of work life balance and burnout on the performance of temporary employees. This analysis uses independent variables, namely work life balance and burnout and the dependent variable, namely performance. The sample of this study was administrative temporary employees of the Faculty of Social and Political Sciences, University of Riau with a total sampling technique. Data collection was carried out by distributing 50 questionnaires directly to temporary employees. Statistical method uses Multiple Linear Regression Analysis with hypothesis testing statistical test F test and T test. The results of this study indicate that partially work life balance and burnout have no significant effect on performance. Simultaneously, work life balance and burnout also have no significant effect on the performance of temporary employees. Some temporary employees are still worried about various things outside of work, including personal life while working. The workload and the feeling that temporary employees have that their life and career will not change causes stress